2012
DOI: 10.1007/s10838-012-9199-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Deterministic or the Indeterministic Description? A Critique of the Literature About Classical Dynamical Systems

Abstract: It can be shown that certain kinds of classical deterministic descriptions and indeterministic descriptions are observationally equivalent. In these cases there is a choice between deterministic and indeterministic descriptions. Therefore, the question arises of which description, if any, is preferable relative to evidence. This paper looks at the main argument in the literature (by Winnie, 1998) that the deterministic description is preferable. It will be shown that this argument yields the desired conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Our results contribute from an empirical point of view to the discussion about the observational equivalence between measure-theoretic deterministic systems and stochastic processes, in which observational equivalence means that deterministic description, when observed, and indeterministic descriptions gives the same predictions (Werndl 2009). Moreover, if the evidence equally supports a deterministic and a stochastic description, there is underdetermination concerning which description is preferable relative to evidence (Werndl 2012). Indeed, Werndl (2009) showed that every stochastic process is observationally equivalent to a deterministic system and many deterministic systems are observationally equivalent to stochastic processes.…”
Section: Discussionmentioning
confidence: 67%
“…Our results contribute from an empirical point of view to the discussion about the observational equivalence between measure-theoretic deterministic systems and stochastic processes, in which observational equivalence means that deterministic description, when observed, and indeterministic descriptions gives the same predictions (Werndl 2009). Moreover, if the evidence equally supports a deterministic and a stochastic description, there is underdetermination concerning which description is preferable relative to evidence (Werndl 2012). Indeed, Werndl (2009) showed that every stochastic process is observationally equivalent to a deterministic system and many deterministic systems are observationally equivalent to stochastic processes.…”
Section: Discussionmentioning
confidence: 67%